Effects of Light Ingress through Ventilation Fan Apertures on Selected Blood Variables of Male Broilers - Olanrewaju , H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2017)
Background and Objective: Increasing broiler house size and ventilation capacity have resulted in increased light ingress through ventilation system component apertures. The effective photoperiod for broilers may create local increases in light intensity, which may also impact broiler’ body homeostasis. This study was conducted to investigate the influence of aperture light ingress in grow-out houses on selected blood variables of male broilers reared to 63 days of age. Materials and Methods: Sixty male broiler chicks were randomly distributed to each of 16 environmentally-controlled rooms (960 total birds). Birds were provided a diet formulated to meet or exceed NRC recommendations with feed and water provided ad libitum. The two treatments consisted of a constant (C) light intensity at 2.5 lx at 16L:8D based on prescriptive intensities in typical heavy broiler lighting programs and a variable (V) light intensity and photoperiod program that was based on field measurements near tunnel fans in a solid walled broiler house. The lighting program to 35 days was identical for both treatments and the treatments were initiated at 36 days. Blood samples were collected from the wing brachial vein of 6 birds per room on day 35 (before treatments) and 63, which were then analyzed immediately for whole blood physiological variables. Selected blood plasma biochemistry, enzyme activities and electrolyte levels were evaluated. Results: In comparison to broilers exposed to a ‘C’ light intensity of 2.5 lx, broilers exposed to ‘V’ lighting that mimicked areas near tunnel fans, had significantly lower levels of pH, Ca2+, K+, CK and higher levels of angap, which were within physiological acid-base ranges. Also, age have significant contributor effects on most selected variables. In addition, blood glucose and plasma corticosterone concentrations were not affected by treatment, suggesting an absence of physiological stress and an uncompromising welfare of the birds. Conclusion: It is concluded that there may be a need to mitigate light ingress through ventilation system components to improve live performance of broilers.